Stimulation of JNK Phosphorylation by the PTTH in Prothoracic Glands of the Silkworm, Bombyx mori - Gu, Shi-Hong; Li, Gen; Hsieh, Hsiao-Yen; Lin, Pei-Ling; Li, Sheng (Frontiers in Physiology, 2018)
In this study, phosphorylation of c-Jun N-terminal kinase (JNK) by the prothoracicotropic hormone (PTTH) was investigated in prothoracic glands (PGs) of the silkworm, Bombyx mori. Results showed that JNK phosphorylation was stimulated by the PTTH in time- and dose-dependent manners. In vitro activation of JNK phosphorylation in PGs by the PTTH was also confirmed in an in vivo experiment, in which a PTTH injection greatly increased JNK phosphorylation in PGs of day-6 last instar larvae. JNK phosphorylation caused by PTTH stimulation was greatly inhibited by U73122, a potent and specific inhibitor of phospholipase C (PLC) and an increase in JNK phosphorylation was also detected when PGs were treated with agents (either A23187 or thapsigargin) that directly elevated the intracellular Ca2+ concentration, thereby indicating involvement of PLC and Ca2+. Pretreatment with an inhibitor (U0126) of mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) kinase (MEK) and an inhibitor (LY294002) of phosphoinositide 3-kinase (PI3K) failed to significantly inhibit PTTH-stimulated JNK phosphorylation, indicating that ERK and PI3K were not related to JNK. We further investigated the effect of modulation of the redox state on JNK phosphorylation. In the presence of either an antioxidant (N-acetylcysteine, NAC) or diphenylene iodonium (DPI), PTTH-stimulated JNK phosphorylation was blocked. The JNK kinase inhibitor, SP600125, markedly inhibited PTTH-stimulated JNK phosphorylation and ecdysteroid synthesis. The kinase assay of JNK in PGs confirmed its stimulation by PTTH and inhibition by SP600125. Moreover, PTTH treatment did not affect JNK or Jun mRNA expressions. Based on these findings, we concluded that PTTH stimulates JNK phosphorylation in Ca2+- and PLC-dependent manners and that the redox-regulated JNK signaling pathway is involved in PTTH-stimulated ecdysteroid synthesis in B. mori PGs.